Synthesis, Characterization, and Biological Activity of a Novel Series of Benzo[4,5]imidazo[2,1-b]thiazole Derivatives as Potential Epidermal Growth Factor Receptor Inhibitors - Xinshan Deng; Xiaoyu Tan; Tiantian An; Qingqing Ma; Zhe Jin; Ce Wang; Qingguo Meng; Chun Hu (Molecules, 2019)
Based on the analysis of epidermal growth factor receptor (EGFR) complexes with gefitinib with molecular docking, the scaffold-hopping strategy, combination of the active substructures, and structural optimization of EGFR inhibitors, a novel series of benzo[4,5]imidazo[2,1-b]thiazole derivatives was designed, synthesized, and evaluated for antitumor activity in human cancer cell lines and cellular toxicity against human normal cell lines using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) colorimetric assay and EGFR inhibitory activities in vitro. Some target compounds such as 2-(benzo[4,5]imidazo[2,1-b]thiazol-3-yl)-N-(2-hydroxyphenyl)acetamide (D04) and 2-(benzo[4,5]imidazo[2,1-b]thiazol-3-yl)-N-(naphthalen-1-yl)acetamide (D08) have shown significant antitumor activity against the EGFR high-expressed human cell line HeLa. All the target compounds showed hardly any antitumor activity against the EGFR low-expressed human cell line HepG2, and nearly no cellular toxicity against the human normal cell lines HL7702 and human umbilical vein endothelial cell lines (HUVEC). The inhibitory activities against EGFR kinase in vitro of the three target compounds were greatly consistent with the anti-proliferative activities. The preliminary structure⁻activity relationships of the target compounds were summarized. Conclusively, the novel benzo[4,5]imidazo[2,1-b]thiazole derivatives as novel potential EGFR inhibitors may be used as the potential lead compounds for the development of antitumor agents.